Aplikasi Layanan Pengaduan Masyarakat Desa Tanjung Dalam Menggunakan Metode Fuzzy Berbasis Android - TAKDIR ALISYAHBANA; Andri (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2022)
Public complaints are an important element in government agencies, because complaints aim to improve the shortcomings of activities that have been carried out by the government. Public complaints in Tanjung Dalam Village have not been fully published, so people are confused about where to complain. The method used in this study is the Weighted Product. This method is a Fuzzy Multiple Attribute Decision Making (FMADM) method to determine priorities or rankings. The conclusion of this research is that this Public Complaint Service Application can be used as a medium to complain about events experienced by the Tanjung Dalam Village community in responding to public complaints more effectively and efficiently than the manual method. Keywords— Community Complaint Service, Android, Fuzzy Method, Firebase